APPLICATION OF 5S (SEIRI, SEITON, SEISO, SEIKETSU, SHITSUKE) IN THE MOBILE SHOP WORK AREA AS AN EFFORT TO INCREASE WORK PRODUCTIVITY (CASE STUDY AT PT XYZ) - Wahyu Wiguna; Budi Susanto; Martinus Tukiran (Yayasan Education and Social Center, 2022)
Brown paper and white paper are the two primary products manufactured at PT XYZ Mobile Shop Work Area, which is one of the supporting heavy industry operations engaged in the manufacturing of industrial goods. The finding of problems in the work area revealed that heavy equipment, specifically forklifts and trucks, has been damaged and is being stored together with normal ones. It is being done on purpose because there are parts that can cannibalize. Consequently, the space available to workers is limited, and neither management nor supervisors can regulate the working environment or ensure worker safety. In this study, we will compare the 5S design to the conditions that are currently in place. For this study, a qualitative approach known as the 5S method choose to conduct the research. As part of designing the layout for the seiton stage, the goods classify according to the shape they assume. The seiketsu location designing to provide visual control through labelling, marking, and area boarding to facilitate functionality. The shitsuke stage design carries out through activity execution by incorporating the 5S rule into the company's standard activity system. Following the completion of the maintenance, the working time can be reduced from 420 minutes to 405 minutes, representing a 4% reduction in total working time. Otif data to see work productivity in September and October 2022 averaged 96.15%, whereas the productivity / Otif value was only 91.60% in April 2022. Productivity increased slightly in September and October 2022, reaching 96.23% and 96.08%, respectively